School Efforts in Implementing the SMART (Polite, Independent, Active, Religious and Skilled) Program at SD Negeri Kepuharjo 01 Lumajang - Khoirunida, Marsa Rafila; Maisyaroh, Maisyaroh; Supriyanto, Achmad; Juharyanto, Juharyanto (Proceedings Series of Educational Studies, 2024)
Character education is a process of personality formation, ways of thinking and human behavior which will later become a moral foundation in social life. This is why the goals of education at all levels are closely related to the formation of students' character. The application of character education, especially at the elementary school level, is to form and develop potential in students so that they can have values and character both in terms of culture and nation. This research aims to; (1) describe the school's efforts in implementing the GSM (Quran School Movement) activities; (2) to describe the school's efforts in implementing the Kepusa Got Talent activities; (3) to describe the school's efforts in implementing the Kepusa Berhias activities; (4) to describe the overall results of the SMART program. Keywords: school efforts; implementation; character building; SMART; student